Euro area monetary policy and TARGET balances: A trilogy - Jens Eisenschmidt; Danielle Kedan; Martin Schmitz (European Central Bank (ECB), 2022)
The growth in TARGET balances after 2009 has given rise to intense academic and public debate. Our paper offers a systematic exposition of the necessary conditions for TARGET balances to emerge and provides a clear link to monetary policy. We show that large TARGET balances can only arise with excess liquidity. The interpretation of TARGET balances therefore depends on the monetary policy context in which excess liquidity is created. We distinguish three phases of TARGET balances growth and propose some easy-to-derive metrics for policy makers and academics to assess developments in TARGET balances. We develop a comprehensive econometric framework to account for relevant factors driving TARGET balances in the different phases. We find that while financial market stress and economic imbalances were the drivers of TARGET balances during the great financial and sovereign debt crises, the implementation of Eurosystem asset purchases was the driving force since March 2015. As excess liquidity is likely to persist on account of higher demand for central bank reserves compared to the pre-crisis period, TARGET balances have the potential to remain sizeable in the future.
Keywords: E42; E58; F32; 330; TARGET2; asset purchase programme; excess liquidity; balance of payments